Kewenangan Badan Penyelesaian Sengketa Konsumen dalam Menangani Sengketa Wanprestasi Antara Konsumen dengan Pelaku Usaha - Demak Setio Laksono (LPPM Universitas Ekasakti Padang, 2023)
Technology sustainability and industrial revolution create numerous of changes which one is commerce or trading especially on mechanism or scheme of sale-purchase between consumer and producer (entrepreneur). Effect of it is also make an impact to convenience for entrepreneur or seller for their trading and marketing. To avoid entrepreneur that exploit the circumstance and protecting consumer, Government regulate and legalize regulation number 8 1999 concerning Consumer Protection. By regulation and legalization, Government restricts entrepreneur act in order to not do faulty and bad faith that can damage consumer direct or indirectly. If there are any loss of consumer, Regulation number 8 1999 concerning Consumer Protection provide forum of dispute settlement through Consumer Dispute Settlement Body (BPSK). In civil law, civil dispute divides to be Act Against Law (PMH) and Breach of Contract, it means BPSK can settle PMH and Breach of Contract. In fact, there are exist any awards of state district court in Indonesia that stipulates BPSK is not have authority to hearing and deciding Breach of Contract. In conclusion, arises assumption or opinion that ambiguity of BPSK authority for hearing and deciding Breach of Contract.